-4n(6n-5)+3n=

Simple and best practice solution for -4n(6n-5)+3n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n(6n-5)+3n= equation:


Simplifying
-4n(6n + -5) + 3n = 0

Reorder the terms:
-4n(-5 + 6n) + 3n = 0
(-5 * -4n + 6n * -4n) + 3n = 0
(20n + -24n2) + 3n = 0

Reorder the terms:
20n + 3n + -24n2 = 0

Combine like terms: 20n + 3n = 23n
23n + -24n2 = 0

Solving
23n + -24n2 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), 'n'.
n(23 + -24n) = 0

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0

Subproblem 2

Set the factor '(23 + -24n)' equal to zero and attempt to solve: Simplifying 23 + -24n = 0 Solving 23 + -24n = 0 Move all terms containing n to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -24n = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -24n = 0 + -23 -24n = 0 + -23 Combine like terms: 0 + -23 = -23 -24n = -23 Divide each side by '-24'. n = 0.9583333333 Simplifying n = 0.9583333333

Solution

n = {0, 0.9583333333}

See similar equations:

| 5(x+3)=4x+14 | | 0.9x-5.3=0.1 | | (9x-6)+6= | | 2+-6m=-4m+10 | | -9(y-1)=2-8y | | -3x(x+5)-7=-8+10 | | 3a-(5-3a)=10 | | 4(q)+(-1)(1-q)=1q+2(1-q) | | 5x+-6=3x+-8 | | (3-x)+(x-4)=2(x+4) | | w=-125t+6000 | | -6+5(-9x-3)=-10 | | -6+(-9x-3)=-10 | | 24+r=28 | | 5p+8=-32 | | 2=-19+z | | 6m-4=4m | | 2=-4+k | | 18p^3-63p^2-9p=0 | | 4x^2+8x+48y-44=0 | | -7(2x-8)+3=-14x+59 | | 10-4=16 | | Q-3=25 | | F(x)=ln(x)*x^2 | | 66=10-8b | | K-12=11 | | b/2=-7 | | 4b+3a= | | 1-2r=9-r | | 12x^4-26x^3+10x^2=0 | | 9x-2=9(x+8) | | 8=6-p(p+3) |

Equations solver categories